Isolated and dependent: women and children in high-rise social housing in post-war Glasgow. Issue 5 (29th July 2019) - Abrams, Lynn; Fleming, Linda; Hazley, Barry; Wright, Valerie; Kearns, Ade
ABSTRACT: In 1971 Pearl Jephcott's Homes in High Flats, the culmination of her groundbreaking research into high rise living in Glasgow, revealed the problems faced by young mothers on the new high rise estates in the city. This article interrogates two connected factors, social isolation and economic dependence, which characterised the experience of many women who were rehoused to high flats in the postwar decades. Drawing on evidence collected by Jephcott's research in the form of qualitative questionnaires with high rise tenants as well as ethnographic observation and action research with residents, we argue that the experience of many women of managing everyday life in a high rise flat with young children was frustrating, often lonely and unsupported, at a time when the home was still conceptualised as central to women's lives. Jephcott asserted that high rise housing had socially negative consequences for women and children. We do not disagree but argue that in the particular context of the postwar settlement, women's financial and welfare dependence on top of their particular housing circumstances in high rise flats constrained their opportunities rather than producing contentment thereby demonstrating the value of revisiting social research data.